Methyl Jasmonate Alleviated the Adverse Effects of Cadmium Stress in Pea (Pisum sativum L.): A Nexus of Photosystem II Activity and Dynamics of Redox Balance - Manzoor, Hamid; Mehwish,; Bukhat, Sherien; Rasul, Sumaira; Rehmani, Muhammad Ishaq Asif; Noreen, Sibgha; Athar, Habib-ur-Rehman; Zafar, Zafar Ullah; Skalicky, Milan; Soufan, Walid; Brestic, Marian; Habib-ur-Rahman, Muhammad; et al. (Frontiers in Plant Science, 2022)
The accumulation of cadmium (Cd) in leaves reduces photosynthetic capacity by degrading photosynthetic pigments, reducing photosystem II activity and producing reactive oxygen species (ROS). Though it was demonstrated that the application of Methyl Jasmonate (MeJA) induces heavy metal (HM) stress tolerance in plants, its role in adjusting redox balance and photosynthetic machinery is unclear. In this study, the role of MeJA in modulating photosystem II (PSII) activity and antioxidant defence system was investigated to reduce the toxic effects of Cd on the growth of pea (Pisum sativum L.) cultivars. One-week-old seedlings of three pea varieties were subjected to Cd stress (0, 50, 100 uM), and MeJA (0, 1, 5, 10 uM) was applied as a foliar spray for two weeks. Cadmium stress reduced the growth of all three pea varieties. Cadmium stress decreased photosynthetic pigments [Chl a (58.15%), Chl b (48.97%), total Chl (51.9%) and carotenoids (44.01%)] and efficiency of photosystem II [Fv/Fm (19.52%) and Y(II) (67.67%)], while it substantially increased Cd accumulation along with an increase in ROS (79.09%) and lipid peroxidation (129.28%). However, such adverse effects of Cd stress varied in different pea varieties. Exogenous application of MeJA increased the activity of a battery of antioxidant enzymes [superoxide dismutase (33.68%), peroxidase (29.75%) and catalase (38.86%)], improved photosynthetic pigments and PSII efficiency. This led to improved growth of pea varieties under Cd stress, such as increased fresh and dry weights of shoots and roots. In addition, improvement in root biomass by MeJA was more significant than that of shoot biomass. Thus, the mitigating effect of MeJA was attributed to its role in cellular redox balance and photosynthetic machinery of pea plants when exposed to Cd stress.